A influência da orientação corporal nos movimentos de cabeça em lactentes a termo e pré-termo aos 5-6 meses de idade - Maia, Michele Gonçalves (Universidade Federal de São Carlos, 2016)
Motor development is a process of changes in motor behavior over time, due to an interaction of systems within the organism, the environment and tasks. The presence of risk factors, such as prematurity, may influence motor development, including the control of head movements. In this context, some strategies may prevent delay in the acquisition of head control, which is required for more complex abilities. Postural manipulation may be a strategy to improve head control in preterm infants, as it is known that postural manipulation may facilitate more mature head movements in full-term infants between birth and four months of age. Objective: To assess the influence of postural manipulation on head movements in full-term and late preterm infants at 5-6 months of corrected age. Method: Thirty eight infants (22 full-term infants and 16 late preterm infants, born at 34-36 weeks gestation) were assessed in a infant chair once in three experimental conditions: a) unsupported supine, b) supported supine (small pillow as an external support), and c) supported reclined at an angle of 20 degrees (small pillow). To elicit head movements, a black and white smiley face card was manually moved from side to side in the infant’s visual field for two minutes in each posture. A two-way repeated measures ANOVA was conducted to compare the groups and conditions (p <0.05). Results: We found that body orientation or external support influenced the control of head movement however in a different way than expected, possibly because at these ages infants have acquired strength and control enough for the task even in the most demanding postures at neuromotor and biomechanical level. No difference was observed between the experimental conditions for most variables, however, the use of support promoted more controlled movements. There was a difference for the desaceleration index (F [1.44]= 4.741; p=0.01), which the preterm infants presented higher values than full-term infants in supported supine position (p=0,012). Moreover, for the preterm infants, they presented higher values in the supported supine compared to the unsupported supine, and supported reclined (p = 0.007 and p = 0.003 , respectively). Conclusion:. We suggest the external support of the head promoted more controlled head movements in preterm infants. These findings suggested posture manipulation may be an early intervention strategy for infants at risk for developmental delay.
Keywords: Desenvolvimento; Orientação corporal; Controle de cabeça; Prematuridade; Intervenção precoce; Child development; Posture manipulation; Head movements; Preterm; early intervention; CIENCIAS BIOLOGICAS; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL